A NEW SPECTROPHOTOMETRIC PROCEDURE FOR THE DETERMINATION OF NICKEL (11) USING 6-PHENYL-2,3-DIHYDRO-AS-TRIAZINE-3 –THIONE (Journal of Sciences, Islamic Republic of Iran)
A spectrophotometric procedure for the determination of Nickel (??) based on the complex formation with 6-phenyl-2, 3-dihydro-as-triazine-3-thione (PDTT) was developed. A yellow compound forms and is easily extractable by chloroform at pH>6. The mole ratio between Nickel (??) and PDTT is 1:4. The absorbance of the complex obeys Beer's law over the concentration range of 1-7 ug of Ni (??) per ml chloroform. This procedure can be carried out in the presence of many cations and anions without appreciable interference.